2017
DOI: 10.1038/s41598-017-01507-8
|View full text |Cite
|
Sign up to set email alerts
|

Shorter lifetime of a soil invertebrate species when exposed to copper oxide nanoparticles in a full lifespan exposure test

Abstract: Toxicity tests that last the all life duration of the organisms are not common, instead, long-term tests usually include one reproductive cycle. In the present study we optimized and propose a lifespan (all life) term test using Enchytraeus crypticus (Oligochaeta). The effect of copper oxide nanoparticles (CuO-NPs) was assessed in this lifespan test and compared to copper salt (CuCl2), using the same effect concentrations on reproduction (EC50). Monitored endpoints included survival and reproduction over-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…In most published ecotoxicological studies, the authors have reported the characteristics of nanoparticles in stock/working solutions, namely because soil is a relatively complex medium, [39][40][41][42][43]. In the present study, the hydrodynamic size and the surface charge of the SiO 2 NPs were assessed in ultrapure water, at the concentrations used in the avoidance assays.…”
Section: Discussionmentioning
confidence: 96%
“…In most published ecotoxicological studies, the authors have reported the characteristics of nanoparticles in stock/working solutions, namely because soil is a relatively complex medium, [39][40][41][42][43]. In the present study, the hydrodynamic size and the surface charge of the SiO 2 NPs were assessed in ultrapure water, at the concentrations used in the avoidance assays.…”
Section: Discussionmentioning
confidence: 96%
“…As shown, exposure to copper oxide nanomaterials at the reproduction EC 50 caused shorter longevity than exposure to copper-salt, bringing a novel concept to ecotoxicology (Gonçalves et al, 2017).…”
Section: Enchytraeid Toxicity Studies: Enchytraeus Crypticus/enchytramentioning
confidence: 99%
“…It has been given considerable focus and has currently an extensive suite of tools available for hazard assessment, far beyond the standard ecotoxicity test battery of many other species. The tools cover bioaccumulation (Amorim et al, 2011), avoidance (Bicho et al, 2015a), full life cycle test (Bicho et al, 2015b(Bicho et al, , 2016(Bicho et al, , 2017aSantos et al, 2017), embryotoxicity (Gonçalves et al, 2015), full life span (Gonçalves et al, 2017), multigenerational (Bicho et al, 2017b), multispecies (mesocosm) system (SMS) (Menezes-Oliveira et al, 2013), full transcriptome and microarray tool (Castro-Ferreira et al, 2014;Gomes et al, 2017), oxidative stress biomarkers (Ribeiro et al, 2015), energy metabolism and cellular energy allocation , genotoxicity via the comet assay (Maria et al, 2017), and metabolomics and proteomics. This species has further potential as it can be exposed via water for a short period and hence allows the assessment of other routes of exposure (Gomes et al, 2015b).…”
Section: Enchytraeid Toxicity Studies: Enchytraeus Crypticus/enchytramentioning
confidence: 99%
“…For those studies that have been conducted in natural soil environment, most have presented evidence that Cu ENM are generally less toxic then their bulk or ionic counterparts 27,39,52,69 (Chapter 2:, though there is no consensus on this 68,24,69 . Regardless, it is clear that understanding the fate of the Cu ENM in both the soil and exposed organism is needed to understand or assess the risk an ENM may pose in the soil environment.…”
Section: Introductionmentioning
confidence: 99%
“…A study, which compared effects of ), found that organisms had shorter lifespan, delayed reproduction and, produced fewer juveniles when exposed to nCuO . The authors concluded that since they could not definitively correlate the observed reproduction effects to measured available Cu 2+ (using Cu ISE) in soil pore-water over 28 d, a nano-specific effect may have been possible64 . SP-ICP-MS results from a side experiment, which was conducted to investigate the potential presence of CuNPs in the exposure media, revealed that nano-particulate Cu was detected in all nCuO and CuSO4 treatments analyzed.…”
mentioning
confidence: 99%